2020
DOI: 10.1093/ofid/ofaa443
|View full text |Cite
|
Sign up to set email alerts
|

Global Seasonality of Human Coronaviruses: A Systematic Review

Abstract: In the context of the Covid-19 pandemic, we aimed to systematically address the global seasonal patterns of human coronavirus (HCoV) infections. We identified relevant articles from MEDLINE, EMBASE, and CINAHL Plus as of May 11, 2020. The main outcomes were the peak months of HCoV infections each year, and the months during which more than 5% of positive respiratory specimen tests were attributable to HCoV. Of 707 articles reviewed, 22 met the inclusion criteria. The annual percentage of HCoV infections reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 41 publications
5
53
0
Order By: Relevance
“…Seasonality can induce variations in vital signs including body temperature, blood pressure 28 , and in turn these can affect and influence the different disease populations (e.g., diabetes, cardiovascular, obesity, and others) 29 31 . A seasonal variation of deaths from corona viruses was also observed recently 32 . Thus, the months/seasons may have important interactions with the vital signs beyond the known seasonal susceptibility to influenza.…”
Section: Discussionsupporting
confidence: 53%
“…Seasonality can induce variations in vital signs including body temperature, blood pressure 28 , and in turn these can affect and influence the different disease populations (e.g., diabetes, cardiovascular, obesity, and others) 29 31 . A seasonal variation of deaths from corona viruses was also observed recently 32 . Thus, the months/seasons may have important interactions with the vital signs beyond the known seasonal susceptibility to influenza.…”
Section: Discussionsupporting
confidence: 53%
“…Recent studies have demonstrated the cross-reactivity of the endemic hCoVs induced pre-existing humoral and cellular immune responses with SARS-CoV-2 [ [30] , [31] , [32] ], but at what extent these responses influence the course of the infection or the severity of the disease, is not fully understood. We found significantly better SARS-CoV-2 cross-reactivity in the sera of children, with high endemic hCoV burden [ 7 ]. Interestingly, Tso et al [ 30 ] found a correlation between pre-pandemic sera SARS-CoV-2 cross-recognition and low incidence of SARS-CoV-2 infection in sub-Saharan Africa, where the incidence of endemic hCoVs is high.…”
Section: Discussionmentioning
confidence: 99%
“…There are four circulating endemic hCoVs, 229E, NL43, OC43 and HKU1, the two former are classified to alpha-, and the two latter to beta-CoVs [ 2 ]. These low-pathogenic hCoVs are causative agents in approximately 5% of respiratory tract infections globally [ 7 ], affecting especially children under 10 years of age [ [7] , [8] , [9] , [10] ]. Although endemic hCoVs are randomly detected in the nasal swabs and stools of hospitalized children, they are considered to play a marginal role in severe pediatric respiratory infections [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent systematic review by Park et al ( 22 ) revealed a consistent winter peak of sCoV incidence in the northern hemisphere (akin to other respiratory viruses), with moderate decrease during the summer months. It has to be noted that there is a substantial variation in the percentage of sCoVs infections in different epidemiological studies that appraised patients with acute respiratory infections.…”
Section: An Overview and Global Trendsmentioning
confidence: 99%